Low-dose stavudine trials: a public health priority for developing countries - W D Francois Venter; Steve Innes; Mark Cotton (AOSIS, 2012)
The debate around relooking at stavudine dosing, both in terms of the adult low-dose stavudine study and more broadly, is welcome. The study being proposed to evaluate low-dose stavudine v. tenofovir is a fairly standard placebo-controlled non-inferiority study. The study design is not controversial; however, the choice of study drug has attracted critical attention.